PELATIHAN PENGEMBANGAN FLIPPED CLASSROOM BERBASIS HIGHER-ORDER THINKING SKILLS (HOTS) DAN KURIKULUM MERDEKA BAGI MGMP BAHASA INGGRIS SMA KABUPATEN KUBU RAYA - Ryani Yulian; Ufi Ruhama'; Syarifah Putri Agustini Alkadri (Universitas Mataram, 2023)
The structure of the Merdeka Curriculum necessitates teachers to be at the forefront of their competency. The constraints posed by limited resources in various schools within Kabupaten Kubu Raya encapsulate challenges in devising English language education centered on technology-driven, higher-order thinking. Hindered by restricted internet accessibility and constrained mobility, the MGMP for high school English teachers in Kubu Raya must evolve into a platform for exchanging optimal teaching methods, with a targeted emphasis on content that aligns with the requirements of the Merdeka Curriculum and digital innovation. This community service endeavor aspires to furnish instruction in a HOTS-oriented pedagogical model that corresponds with the Merdeka Curriculum and, additionally, create instructive videos conducive to the flipped classroom technique. The methodology encompasses fostering communal development for English Teacher MGMPs situated in Kubu Raya Regency, encompassing: (1) Instruction and guidance in designing materials for English subjects and HOTS-imbued questions, and ( 2) Training aimed at producing educational videos for the flipped classroom. The results of this community service encompass an impressive 80% of teachers’ competence in terms of methods in higher-order thinking skills activities, project-based learning, and the use of level of learning of Bloom's Taxonomy. Furthermore, this activity also facilitates the teachers to create educational videos for flipped classroom. This community also contributes application for teaching English with videos, pedagogic materials, quizzes, and evaluations. By executing this initiative, the MGMP forum can emerge as a model example for producing educational media in sync with the educational needs of students within the transformative milieu of 21st-century pedagogy.